ISTIKHDÂM AL-TA’ÂBÎR AL-ISHTHILÂHIYYAH WA AL-SIYÂQIYYAH LI AL-MUTA’ALLIQ BI HURÛF AL-JARR FÎ RASÂIL THALABAH AL-BAKÂLÛRIÛS BI KULIYYAH AL-TARBIYAH BI JÂMI’AH SUNAN GUNUNG DJATI BANDUNG - Dedih Wahyudin; Nanang Kosim (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2020)
This study aims to determine the errors of students in using contextual and idiomatic expressions in Arabic student theses of Education Faculty of UIN Sunan Gunung Djati Bandung and to describe the factors that influence the errors. The method used is content analysis and data was analyzed qualitatively. All contextual and idiomatic expressions in the theses of students will be analyzed and combined with Arabic dictionary. Data source is 20 students’ theses. The results showed that errors are still found in contextual and idiomatic expressions, so the meaning of the sentence is not appropriate. The students got difficulties to distinguish both contextual expression and idiomatic expression of huruf jarr usage in writing sentences. The function of huruf jarr is still strange for them. Basicly, it was influenced by several factors, mainly the influence of Indonesian language which is very dominant, in addition to the fact that less students are given sufficient training to use huruf jarr.